Uncovering Accounting in the Pasaji Ponan Tradition: An Ethnographic Study in Sumbawa Tribe - Safira, Rosalinda Yulian; Sokarina, Ayudia (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to reveal and understand how accounting practices are implemented in the tradition of pasaji ponan in Sumbawa tribal communities. This research uses interpretive paradigm and ethnography as the research methodology. Data collection techniques were conducted by interview, observation and documentation. The results showed that the stages of pasaji ponan implementation consisted of Management Meeting and General Meeting, Pre-Ponan Tradition Preparation, Art Performance Night, Ponan Party Core Event and Post-Ponan Party Tradition containing cultural accounting values such as gratitude, friendship, togetherness, social care, mutual cooperation, and cultural preservation. This research is expected to open a dialog about the importance of considering local culture in developing a more diverse and contextual accounting system. In addition, this research is an opportunity to promote cultural tourism in Sumbawa by educating visitors about the social and cultural values in Pasaji Ponan.